Forensic characterisation and polymorphism analysis of 16 X-chromosomal STRs in the Jining Han population in Eastern China - Yequan Wang; Ao Gao; Xiudi Hou; Qi Liu; Dan Wang; Zhen Dang (Taylor & Francis Group, 2023)
Background X-chromosomal short tandem repeats (X-STRs) are a useful supplementary approach to analysing autosomal markers in forensics and kinship studies; such markers are not well-characterised in many populations. Aim To investigate population genetic polymorphism and forensic characterisation of 16 X-STRs in the Jining Han population, and analyse genetic relationships with other Chinese populations. Subjects and methods Allele frequencies for 16 X-STR loci were obtained from a sample set of 527 unrelated individuals from the Jining Han population. Population genetic analyses of Jining Han and another 10 reference populations were conducted using phylogenetic tree, principal component analysis and multidimensional scaling. Results We detected 149 alleles, with frequencies ranging from 0.0013 to 0.8242. The combined powers of discrimination in males and females were 0.999999997194774 and 0.999999999999995, respectively. The combined mean exclusion change (MEC)Krüger, MECKishida, MECDesmarais, and MECDesmarais Duos values were 0.999974632649096, 0.999999976997582, 0.999999977013201, and 0.999993755768423, respectively. We detected relatively high genetic homogeneity in populations with similar ethnic or geographic origins, and a close relationship between the Jining Han and Beijing Han populations. Conclusions The present findings indicate that the 16 X-STR loci examined are highly polymorphic in the Han population of Jining, providing useful information for forensic science and population genetics studies.